The Toxicokinetic Profile of Dex40-GTMAC3—a Novel Polysaccharide Candidate for Reversal of Unfractionated Heparin - Sokolowska, Emilia; Kalaska, Bartlomiej; Kaminski, Kamil; Lewandowska, Alicja; Blazejczyk, Agnieszka; Wietrzyk, Joanna; Kasacka, Irena; Szczubialka, Krzysztof; Pawlak, Dariusz; Nowakowska, Maria; Mogielnicki, Andrzej (Frontiers in Pharmacology, 2016)
Though protamine sulfate is the only approved antidote of unfractionated heparin (UFH), yet may produce life threatening side effects such as systemic hypotension, catastrophic pulmonary vasoconstriction or allergic reactions. We have described 40 kDa dextrans (Dex40) substituted with glycidyltrimethylammonium chloride (GTMAC) as effective, immunogenically and hemodynamically neutral inhibitors of UFH. The aim of the present study was to evaluate in mice and rats toxicokinetic profile of the most promising polymer – Dex40-GTMAC3. Polymer was rapidly eliminated with a half-time of 12.5±3.0 min in Wistar rats, and was mainly distributed to the kidneys and liver in mice. The safety studies included the measurement of blood count and blood biochemistry, erythrocyte osmotic fragility and the evaluation of the histological alterations in kidneys, liver and lungs of mice and rats in acute and chronic experiments. We found that Dex40-GTMAC3 is not only effective but also very well tolerated. Additionally, we found that protamine may cause overt hemolysis with appearance of permanent changes in the liver and kidneys. In summary, fast renal clearance behavior and generally low tissue accumulation of Dex40-GTMAC3 is likely to contribute to its superior to protamine biocompatibility. Intravenous administration of therapeutic doses to living animals does not result in the immunogenic, hemodynamic, blood and organ toxicity. Dex40-GTMAC3 seems to be a promising effective and safe candidate for further clinical development as new UFH reversal agent.